2019
DOI: 10.1111/ced.13885
|View full text |Cite
|
Sign up to set email alerts
|

What's new in atopic eczema? An analysis of systematic reviews published in 2016. Part 1: treatment and prevention

Abstract: Summary This review is part of a series of annual updates summarizing the evidence base for atopic eczema (AE). It provides a summary of key findings from 28 systematic reviews that were published or indexed during 2016 with a focus on treatment and prevention of AE. There is reasonable evidence of benefit for topical corticosteroids, calcineurin inhibitors, a glycyrrhetinic acid‐containing preparation (Atopiclair®), oral ciclosporin, oral azathioprine, narrowband ultraviolet B radiation and education programm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…20,41 Findings from 14 systematic reviews published before 2016 observed that persistent atopic dermatitis is associated with more severe disease at the time of diagnosis, onset after the age of two years and being a female. 42 A systematic review in- cluding 45 studies was considered and found that a later onset increased persistence. 43 Some genetic factors have been associated with persistent dermatitis, but these factors are not easy to use in clinical practice.…”
Section: Can Atopic Dermatitis Be Prevented?mentioning
confidence: 99%
“…20,41 Findings from 14 systematic reviews published before 2016 observed that persistent atopic dermatitis is associated with more severe disease at the time of diagnosis, onset after the age of two years and being a female. 42 A systematic review in- cluding 45 studies was considered and found that a later onset increased persistence. 43 Some genetic factors have been associated with persistent dermatitis, but these factors are not easy to use in clinical practice.…”
Section: Can Atopic Dermatitis Be Prevented?mentioning
confidence: 99%
“…Presently, through a set of systematic remedies ranging from emollients to corticosteroids, we are able to manage most of the symptoms of eczema [23]. Although the exact etiology of eczema is still unknown, a combination of genetic and environmental factors is involved.…”
Section: Discussionmentioning
confidence: 99%
“…10 Topical calcineurin inhibitors can improve mild to moderate eczema without the same side effects as steroids. 11 However, this medication is not subsidised by PHARMAC. 12 If these medications are not effective, some oral medications are approved for eczema.…”
Section: Leina Tucker-mastersmentioning
confidence: 99%
“…7,13 The most promising sign of this change is the research effort around new eczema treatments. Solman et al 11 periodically publish a review of the literature around eczema treatments and noted that each year more and more systematic reviews are published on novel treatments and new regimes. Each biologic medication like dupilumab that has found success is one of hundreds of medications devised and tested by pharmaceutical companies.…”
Section: Leina Tucker-mastersmentioning
confidence: 99%